1981
DOI: 10.1016/0304-3959(81)90637-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of capsaicin applied locally to adult peripheral nerve. II. Anatomy and enzyme and peptide chemistry of peripheral nerve and spinal cord

Abstract: (1) Capsaicin solution was applied for 15 min around a 1 cm length of sciatic nerve in the mid upper leg of adult rats. (2) Electron microscopic examinations of the nerve in the treated region after 14 days shows no signs of degeneration of either myelinated or unmyelinated fibres attributable to the capsaicin. (3) Fluoride resistant acid phosphatase FRAP disappears from the central terminals of the treated nerve by 7 days. (4) 1.5 mM capsaicin is sufficient to product a complete reduction of FRAP in the spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(26 citation statements)
references
References 8 publications
3
23
0
Order By: Relevance
“…If capsaicin is applied to a nerve trunk, two weeks later neurogenic or chemogenic inflammatory responses are absent in the territory of that nerve (Jansco, Kiraly & Jansco-Gabor, 1980) and its neuropeptides are depleted (Ainsworth, Hall, Wall, Allt, Lynn Mackenzie, Gibson & Polak, 1981), although there is no significant change in the size of the nerve compound action potential (Wall & Fitzgerald, 1981). One may speculate that there is a constant physiological (possibly trophic) release of peptides from cutaneous sensory nerve terminals, leading in turn to histamine release, and that this process is enhanced by skin (or neurogenic) stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…If capsaicin is applied to a nerve trunk, two weeks later neurogenic or chemogenic inflammatory responses are absent in the territory of that nerve (Jansco, Kiraly & Jansco-Gabor, 1980) and its neuropeptides are depleted (Ainsworth, Hall, Wall, Allt, Lynn Mackenzie, Gibson & Polak, 1981), although there is no significant change in the size of the nerve compound action potential (Wall & Fitzgerald, 1981). One may speculate that there is a constant physiological (possibly trophic) release of peptides from cutaneous sensory nerve terminals, leading in turn to histamine release, and that this process is enhanced by skin (or neurogenic) stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…To more precisely determine whether it was the surgical denervation of WAT via the destruction of its sympathetic innervation or of its sensory innervation (see below), we surgically denervated WAT (positive control) or locally injected 6OHDA to kill only the sympathetic nerves and spare the sensory nerves or locally injected capsaicin to kill the sensory nerves and spare the sympathetics (107). Capsaicin is the pungent part of red chili peppers and also is a selective neurotoxin for unmyelinated sensory nerves (166,167). We verified the destruction of the sympathetics by 6OHDA using immunohistochemistry for TH and the destruction of sensory innervation by capsaicin using immunohistochemistry for CGRP (107).…”
Section: Sns Innervation Of Wat Can Control White Adipocyte Proliferamentioning
confidence: 99%
“…In agreement with previous observations (Ainsworth et al, 1981;Gamse et al, 1982;Jancsó, 1992;Jancsó and Lawson, 1990;Wall, 1987) we found that, in the substantia gelatinosa, TMP activity was virtually completely depleted from the somatotopically related areas of the treated sciatic nerve 2 weeks after the treatment. Other nociceptor specific markers i.e., somatostatin, IB4, SP and TRPV1 also showed marked decreases due to perineural capsaicin treatment (Gamse et al, 1982;Gibson et al, 1982;Knotkova et al, 2008;Molander and Grant, 1986;Sántha and Jancsó, 2003;Szigeti et al, 2012) and similar changes were observed in the spinal dorsal horn after axotomy (Atkinson and Shehab, 1986;Bennett et al, 1998;Jancsó, 1992;Jessel et al, 1979;Michael and Priestley, 1999).…”
Section: Effects Of D-pdmp Treatment On the Neurite Outgrowth Of Cultsupporting
confidence: 93%